2015
DOI: 10.3928/00904481-20150203-11
|View full text |Cite
|
Sign up to set email alerts
|

Options for Pharmacoresistant Epilepsy in Children: When Medications Don’t Work

Abstract: Medications are often first-line treatment for epilepsy in children. A detailed review of antiepileptic drugs and their application in various epilepsy syndromes is provided in the article "Antiepileptic Drugs--A Review" by Sankaraneni and Lachhwani (this issue). Here, we will focus on nonmedicinal approaches-some fairly longstanding and described since Biblical times such as the ketogenic diet while others are relatively new such as neurostimulation. Yet, others such as cannabinoids have been utilized for cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Other patients with multifocal or generalized epilepsy and children with epileptic encephalopathies benefited from genetic testing (a more defined pathway for genetic testing in the clinic can further improve the workflow), medical therapy, neuromodulation, dietary therapy, and palliative surgery. [16,[28][29][30][31]] Interestingly, we observed significantly more patients receiving a recommendation for VNS compared to dietary therapy. It is unclear if regular access of a neurosurgeon in the clinic caused a bias recommendation toward VNS.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other patients with multifocal or generalized epilepsy and children with epileptic encephalopathies benefited from genetic testing (a more defined pathway for genetic testing in the clinic can further improve the workflow), medical therapy, neuromodulation, dietary therapy, and palliative surgery. [16,[28][29][30][31]] Interestingly, we observed significantly more patients receiving a recommendation for VNS compared to dietary therapy. It is unclear if regular access of a neurosurgeon in the clinic caused a bias recommendation toward VNS.…”
Section: Discussionmentioning
confidence: 86%
“…We educated providers about ideal referral candidates, focusing on recognized etiologies and syndromes associated with DRE, such as tumors, mesial temporal sclerosis, cortical dysplasia, hypothalamic hamartoma, and hemispheric syndromes. [16] We also expressly indicated that cases typically perceived as difficult candidates for surgery (e.g., very young age, developmental disabilities, psychiatric issues, lesion overlapping the eloquent cortex, multifocal epilepsy) would not be a contraindication to referral to this clinic. We encouraged earlier referral for younger patients.…”
Section: Patient Identification and Workflowmentioning
confidence: 89%
“…Supplements may be an adjunct to a child's comprehensive pain management plan (Table 2) [127‐149]. Asking families about supplements is important too, as some supplements may interact with other prescribed medications, may have evidence of ineffectiveness, or have the potential to be harmful to the child (Table 2).…”
Section: Complementary and Alternative Medicine (Cam)mentioning
confidence: 99%
“…The potential efficacy of FFA in epilepsies other than Dravet syndrome and LGS is unknown, although a small case series of other epileptic encephalopathy suggested its potential utility in other epilepsy syndromes [ 98 , 99 ]. A pilot clinical trial is ongoing to evaluate FFA’s efficacy in different developmental and epileptic encephalopathies (DEEs) secondary to SYNGAP1 encephalopathy, STXBP1 encephalopathy with epilepsy, inv-dup (15) encephalopathy, cortical malformation, and encephalopathy associated with continuous spikes and waves during sleep.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%